Multi-Level Mixed-Effects Analysis of Stunting Among 6 to 59 Months Children in Ethiopia: Evidenced from Analysis of Health and Demographic Survey, 2000 to 2019 - Haymanot Mezmur PhD; Maleda Tefera PhD; Aklilu Abrham Roba MSc; Öznur Başdaş PhD (SAGE Publishing, 2024)
Background. Stunting remains a major public health issue in developing countries like Ethiopia. It is termed as a chronic malnutrition which leads to morbidity and mortality among children. This study aimed to assess the prevalence and factors associated with stunting among 6 to 59 months children in Ethiopia. Methods. A total weighted sample of 34 930 children aged 6 to 59 months was included in this study. A Multilevel Mixed-Effect logistic regression was carried out. The Median Odds Ratio (MOR) and the Intra class Correlation Coefficient (ICC) were calculated. An adjusted odds ratio along with a 95% confidence interval was reported and statistical significance was declared at a P -value ≤ .05. Results. The weighted prevalence of stunting in Ethiopia was 48.3% (95% CI: 47.8%, 48.8%). Being male, increased in age, having multiple births (twin), having less than 2 years birth interval, history of diarrhea, anemia, lack of maternal and paternal formal education, having poor and middle-wealth status, and living in rural areas were significantly associated with stunting. Conclusions. The prevalence of stunting is high in Ethiopia. The risk factors mentioned above increase the likely hood of stunting among children. Therefore, we recommend that responsible bodies place a greater emphasis and priority on promoting parental education, awareness on the impact of the birth interval on child nutrition, the prevention of childhood diarrhea and anemia, improving household economic status, and reducing rural-urban disparities.